Collectin Liver 1 and Collectin Kidney 1 of the Lectin Complement Pathway Are Associated With Mortality After Kidney Transplantation. Issue 1 (25th July 2016) - Smedbråten, J.; Sagedal, S.; Åsberg, A.; Hartmann, A.; Rollag, H.; Mjøen, G.; Fagerland, M. W.; Hansen, S. W. K.; Mollnes, T. E.; Thiel, S.
Abstract : Kidney transplanted patients still have significantly higher mortality compared with the general population. The innate immune system may play an important role during periods, with suppression of the adaptive immune system. In the present study, two soluble pattern recognition molecules of the innate immune system were investigated, collectin liver 1 (CL‐L1) and collectin kidney 1 (CL‐K1). Potential associations of their pretransplant levels and long‐term graft and recipient survival were examined. The levels of CL‐L1 and CL‐K1 were measured at the time of transplantation in 382 patients (≥17 years) transplanted in 2000–2001. The cohort was subsequently followed until December 31, 2014. Data on patient and graft survival were obtained from the Norwegian Renal Registry. Both high CL‐L1 (≥376 ng/mL) and high CL‐K1 (≥304 ng/mL) levels were significantly associated with overall mortality in multivariate Cox analyses with hazard ration (HR) 1.50, 95% confidence interval (CI) 1.09–2.07, p = 0.013 and HR 1.43, 95% CI 1.02–1.99, p = 0.038, respectively. Moreover, high CL‐K1 levels were significantly associated with cardiovascular mortality. No association between measured biomarkers and death‐censored graft loss was found. Finally, there was a significant correlation between these two collectins, r = 0.83 (95% CI 0.80–0.86). In conclusion, CL‐L1 and CL‐K1 were significantly associated with mortality in kidney transplant recipients. Abstract : An observational cohort study of kidney transplant recipients with follow‐up of nearly 14 years shows an association of high levels of collectin liver 1 and collectin kidney 1 with mortality after kidney transplantation.